2007
DOI: 10.1562/0031-8655(2003)0780496hettck2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxygenation Enhances the Tumor Cell Killing of Photofrin-mediated Photodynamic Therapy¶

Abstract: Tumor hypoxia, either preexisting or as a result of oxygen depletion during photodynamic therapy (PDT) light irradiation, can significantly reduce the effectiveness of PDT‐induced cell killing. To overcome tumor hypoxia and improve tumor cell killing, we propose using supplemental hyperoxygenation during Photofrin‐PDT. The mechanism for the tumor cure enhancement of the hyperoxygenation–PDT combination is investigated using an in vivo–in vitro technique. A hypoxic tumor model was established by implanting mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In this study, however, no significant difference in the delay in tumor regrowth was observed between the KLN205 and the LM8 tumors treated by the 3-h-interval PDT. These differences in the results of the in vitro and in vivo study might be due to the difference in the experimental condition and influence of several factors in the tumor tissue, such as photosensitizer uptake, tissue oxygen concentration, light dose delivered, etc [3,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, no significant difference in the delay in tumor regrowth was observed between the KLN205 and the LM8 tumors treated by the 3-h-interval PDT. These differences in the results of the in vitro and in vivo study might be due to the difference in the experimental condition and influence of several factors in the tumor tissue, such as photosensitizer uptake, tissue oxygen concentration, light dose delivered, etc [3,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the advent of newer photosensitizers and PDT technology has led to a renewed interest in evaluating intrapleural PDT (77). Hyperoxygenation is an effective means to enhance PDT cytotoxicity (78,79). Therefore, it is logical to carry out the intrapleural PDT under hyperbaric oxygenation (HBO) breathing to improve the therapeutic effect (80).…”
Section: Pulmonary and Pleural Mesothelial Cancermentioning
confidence: 99%
“…Therefore, it is considered difficult to ensure the effectiveness of PDT in the deep area of a tumor due to local hypoxia. It has been reported that combination therapy with hyperbaric oxygen was effective to increase oxygen concentrations in the deep tissues of tumors and may enhance the effect of PDT (32,33). Furthermore, it has been estimated that increased blood flow of tumor vessels as a result of treatment may increase the oxygen supply and effectiveness of PDT.…”
Section: -------------------------------------------------Table IV Smentioning
confidence: 99%